Експериментальне та теоретичне дослiдження зарядки вуглецевих наночастинок в ударно-зiгрiтiй плазмi при пiролiзi вуглецевовмiсних молекул - Bronin, S. Y.; Emelianov, A. V.; Eremin, A. V.; Khrapak, A. G.; Mikheyeva, E. Y. (Publishing house "Academperiodika", 2018)
This work is devoted to the experimental and theoretical study of charged carbon nanoparticles formed at the pyrolysis of various carbon-containing substances behind shock waves. The experimental results and the computer simulation of the electrical charging of carbon nanoparticles produced during the pyrolysis of C3O2, CCl4, and C6H6 in shock waves are presented. The measurements of the nanoparticle charge by electric probes, as well as their temperature by emission-absorption spectroscopy and size by LII, were performed simultaneously. The results of simulation show a satisfactory agreement with the experimental data.